IMMUNOMODULATING EFFECTS OF THE PURIFIED HEV B 13 FRACTION ON SEPTIC RATS - ALVES, Maxley Martins (Arq Bras Cir Dig, 2017)
BACKGROUND: Sepsis is a potentially life-threatening complication of an infection that occurs when chemicals released into the bloodstream to fight the infection trigger inflammatory responses throughout the body, especially in the acute phase of the disease, producing excessive pro-inflammatory cytokines, leading to multiple organ injury and death. The Hev b 13 fraction has demonstrated biological activity capable of inducing IL-10 production and shrinking inflammatory disease lesions. AIM: To investigate the immunomodulating effects of the Hev b 13 fraction on septic rats. METHODS: Acinetobacter baumannii was injected into the peritoneal cavity of the animals after sustaining a lesion in the pancreas, with the stomach as an entry point. After 10 h of infection, they were euthanized for blood and lung collection, followed by total and differential leukocyte count, determination of cytokine level and histopathological analysis. RESULTS: Administering a single dose of the Hev b 13 fraction 2 h after sepsis induction significantly decreased total leukocyte count. Higher IL-10 and IL-4 and lower IL-6 production shrank the lung tissue lesions compared to the control groups. CONCLUSION: The Hev b 13 fraction exhibits an anti-inflammatory tendency, with potential for sepsis treatment.